(untitled) (Medical Forum Monthly, 2024)
Pakistan has registered an alarming rise in hepatitis, with 12 million people suffering from hepatitis B and C, mainly, due to spread of the infection in hospitals and usage of unsafe injections, by quacks and qualified doctors alike. “The World Health Organization (WHO) figured out the highest injection-patient ratio in Pakistan worldwide with approximately administration of two billion injections to the patients per year, out of which 80 per cent are unsafe and 90 per cent unnecessary,” said Prof Dr Aftab Mohsin, National Programme Manager, Prime Minister’s Programme for Prevention and Control of Hepatitis, while speaking at a seminar on “Unnecessary use of syringes can cause Hepatitis B & C” jointly organised by Mir Khalil-ur-Rahman Memorial Society and National Programme for Prevention and Control of Hepatitis here at a local hotel on 21st December, 2010.